45.9k views
2 votes
Solve for x. 3(x+2)+2x=-4

User UTeisT
by
6.7k points

2 Answers

3 votes

3(x+2)+2x=-4

5x = -10

x = -2

User Imarcelolz
by
5.2k points
3 votes

Distribute the 3 to both x and 2

3(x + 2) = 3x + 6

3x + 6 + 2x = -4

Combine like terms

(3x + 2x) + 6 = -4

5x + 6 = -4

Isolate the x. Note the equal sign. What you do to one side, you do to the other. Subtract 6 from both sides

5x + 6 (-6) = -4 (-6)

5x = -4 - 6

5x = -10

Divide 5 from both sides

5x = -10

5x/5 = -10/5

x = -10/5

x = -2

-2 is your answer for x

hope this helps

User N Djel Okoye
by
5.7k points